Membrane fluidity and myotonia: Effects of cholesterol and desmosterol on erythrocyte membrane fluidity in rats with 20, 25-diazacholesterol-induced myotonia and on phospholipid liposomes. Issue 2 (February 1984) - Ashraf, J.; Feix, J. B.; Butterfield, D. A.
Abstract : Previous spin-label and electromyographic experiments with rats fed 20, 25-diazacholesterol, an inhibitor of the biosynthetic conversion of desmostero to cholesterol, demonstrated an increased erythrocyte membrane fluidity and myotonia, a prolonged muscle contraction upon stimulation. The current studies with rats showed normal erythrocyte fluidity in animals fed 20, 25-diazacholesterol but maintained on a high-cholesterol diet and no myotonia. Studies of model membrane systems composed of phospholipid vesicles containing desmosterol, cholesterol, or both demonstrated that desmosterol increased membrane lipid fluidity relative to cholesterol, suggesting that in 20, 25-diazacholesterol-induced myotonia, in which desmosterot accounts for 85% of the plasma sterol, the increased membrane fluidity previously observed in erythrocytes and sarcolemma in this animal model of human congenital myotonia may be due to desmosterol.